The Influence of Financial Literacy, Family Environment, and Pocket Money on Student Financial Management at Universitas Muhammadiyah Surakarta - Sisilia, S; Harsono, H (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aims to determine the influence of family environmental financial literacy and pocket money on the financial management of students of the University of Muhammadiyah Surakarta. This research method uses a quantitative approach with the type of research used is comparative causal, using questionnaires shared via google form as an instrument in data collection techniques. The population in this study is students who are or have taken financial management courses, while the object is students of the accounting education study program at the University of Muhammadiyah Surakarta. The data analysis technique used is multiple linear regression analysis and obtains the following results: 1) financial literacy has a positive and significant effect on student financial management, 2) the family environment has a positive and significant effect on student financial management, 3) pocket money has no influence or has a negative influence on student financial management, 4) financial literacy, family environment, and pocket money simultaneously has an influence on student financial management.